2020
DOI: 10.3390/pharmaceutics12111093
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of pH-Responsive Quatsomes from Quaternary Bicephalic Surfactants and Cholesterol for Enhanced Delivery of Vancomycin against Methicillin Resistant Staphylococcus aureus

Abstract: Globally, human beings continue to be at high risk of infectious diseases caused by methicillin-resistant Staphylococcus aureus (MRSA); and current treatments are being depleted due to antimicrobial resistance. Therefore, the synthesis and formulation of novel materials is essential for combating antimicrobial resistance. The study aimed to synthesize a quaternary bicephalic surfactant (StBAclm) and thereof to formulate pH-responsive vancomycin (VCM)-loaded quatsomes to enhance the activity of the antibiotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 113 publications
(153 reference statements)
1
19
0
Order By: Relevance
“…On the other hand, Hanssan et al proposed a three-step synthesis to obtain a quaternary bicephalous cationic surfactant through the Michael reaction, using a different precursor to the previously reported synthetic methods [151]. They used trihexylamine with tert-butylacrylate only using methanol (MeOH) (step 1).…”
Section: Synthesis Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Hanssan et al proposed a three-step synthesis to obtain a quaternary bicephalous cationic surfactant through the Michael reaction, using a different precursor to the previously reported synthetic methods [151]. They used trihexylamine with tert-butylacrylate only using methanol (MeOH) (step 1).…”
Section: Synthesis Pathwaysmentioning
confidence: 99%
“…They used trihexylamine with tert-butylacrylate only using methanol (MeOH) (step 1). The product obtained reacts with triisopropylsilane (TIPs) and trifluoroacetic acid (TFA) (step 2), and finally the On the other hand, Hanssan et al proposed a three-step synthesis to obtain a quaternary bicephalous cationic surfactant through the Michael reaction, using a different precursor to the previously reported synthetic methods [151]. They used trihexylamine with tert-butylacrylate only using methanol (MeOH) (step 1).…”
Section: Synthesis Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of current antibiotics with various self-targeting platforms generating ROS inside an infectious biofilm or delivering antibiotics into the depth of a biofilm, has provided a new means to kill multi-drug resistant bacteria. 55,56 Therewith, a direly-needed pathway for future research has been lined out for the control of antimicrobial-resistant infections through the use of self-targeting nano-antimicrobials and nanocarriers, very similar to the pathway applied for the control of malignant tumors. 2,57 The next challenge with respect to bacterial infection control will be the translation of self-targeting nanoantimicrobials and antimicrobial nanocarriers from successful animal experiments to human clinical trials and application.…”
Section: Clinical Merits Of Self-targeting Versus Targeting Platforms...mentioning
confidence: 99%
“…However, when the porphyrin was loaded to a cationic liposome, the phototoxicity effects against the bacteria increased remarkably. The increased effect upon loading the synthesized porphyrin in the cationic delivery system was attributed to the increased positive charge density ( Hassan et al, 2020 ) that destroyed the bacterial wall, thereby enhancing the permeability of the photosensitizer. A similar study was reported by Bombelli and co-workers ( Bombelli et al, 2008 ).…”
Section: Advancement Of Porphyrin-based Photosensitizers For Targetedmentioning
confidence: 99%